Social effects for locomotion vary between environments in Drosophila melanogaster females. (1st July 2017) - Signor, Sarah A.; Abbasi, Mohammad; Marjoram, Paul; Nuzhdin, Sergey V.
Abstract: Despite strong purifying or directional selection, variation is ubiquitous in populations. One mechanism for the maintenance of variation is indirect genetic effects (IGEs), as the fitness of a given genotype will depend somewhat on the genes of its social partners. IGEs describe the effect of genes in social partners on the expression of the phenotype of a focal individual. Here, we ask what effect IGEs, and variation in IGEs between abiotic environments, has on locomotion in Drosophila . This trait is known to be subject to intralocus sexually antagonistic selection. We estimate the coefficient of interaction, Ψ, using six inbred lines of Drosophila . We found that Ψ varied between abiotic environments, and that it may vary across among male genotypes in an abiotic environment specific manner. We also found evidence that social effects of males alter the value of a sexually dimorphic trait in females, highlighting an interesting avenue for future research into sexual antagonism. We conclude that IGEs are an important component of social and sexual interactions and that they vary between individuals and abiotic environments in complex ways, with the potential to promote the maintenance of phenotypic variation.